Comparison of line width calibration using critical dimension atomic force microscopes between PTB and NIST. (19th April 2017) - Dai, Gaoliang; Hahm, Kai; Bosse, Harald; Dixson, Ronald G
Abstract: International comparisons between National Metrology Institutes are important to verify measurement results and the associated uncertainties. In this paper, we report a comparison of the line width calibration of a crystalline silicon line width standard, referred to as IVPS100-PTB standard, between the Physikalisch-Technische Bundesanstalt in Germany and the National Institute of Standards and Technology in the United States. Critical dimension atomic force microscopy was the measurement method used for this comparison. Both institutes applied generally the same but independently developed traceability pathways: the scaling factor of the atomic force microscope (AFM) scanner was calibrated by a set of step height and lateral standards certified by metrological AFMs, while the effective tip width was ultimately traceable to the lattice parameter of silicon via high resolution transmission electron microscopy. Good agreement has been achieved in the comparison: For two groups of line features with nominal critical dimensions (CDs) of 50 nm, 70 nm, 90 nm, 110 nm and 130 nm that were compared, the observed deviations of CD results were between  −1.5 nm and 0.3 nm. The deviations are well within the associated measurement uncertainty.